From impact metrics and open science to communicating research: Journalists’ awareness of academic controversies - Alice Fleerackers; Laura L. Moorhead; Juan Pablo Alperin; Michelle Riedlinger; Lauren A. Maggio (PLoS ONE, 2025)
This study sheds light on how journalists respond to evolving debates within academia around topics including research integrity, improper use of metrics to measure research quality and impact, and the risks and benefits of the open science movement. It does so through a codebook thematic analysis of semi-structured interviews with 19 health and science journalists from the Global North. We find that journalists’ perceptions of these academic controversies vary widely, with some displaying a highly critical and nuanced understanding and others presenting a more limited awareness. Those with a more in-depth understanding report closely scrutinizing the research they report, carefully vetting the study design, methodology, and analyses. Those with a more limited awareness are more trusting of the peer review system as a quality control system and more willing to rely on researchers when determining what research to report on and how to vet and frame it. While some of these perceptions and practices may support high-quality media coverage of science, others have the potential to compromise journalists’ ability to serve the public interest. Results provide some of the first insights into the nature and potential implications of journalists’ internalization of the logics of science.